Building Literacy of Early Age Students' Language; Teacher Managerial Competence and Legal-Rational Authority of Boarding School Leaders - Nisa Fitriani; Syamsul Anam; Asep Maulana; Sebgag, Saliha (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2024)
This article aims to analyze and find the authority of boarding school leaders and the managerial competence of teachers in constructing language literacy awareness in the Imam Syafi'i Islamic Boarding School, Jember Regency. This research uses a qualitative type with a descriptive exploratory approach—data collection techniques using in-depth interviews, participatory observation, and documentation studies. The data were then analyzed using the stages of data reduction, data presentation, and concluding with the validity of the data, the credibility of the triangulation method and sources, and confirmability. Based on the research findings, it was concluded that STDI teacher Imam Syafi'i carries out his role as the authority in compiling programs, organizing language literacy teams, mobilizing teaching staff and staff, optimizing Islamic boarding schools' resources, and controlling activities through monitoring activity processes and achievement of religious literacy programs and utilizing monitoring results in increasing progress quality of students with sustainable language literacy programs.